Effect of Maternal Anemia on the Anthropometric Indices of Newborn - Shah, Tazeen; Warsi, Jamshed; Laghari, Zulfiqar (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To study the effect of maternal anemia on the anthropometric indices of newborn. Methodology: This cross-sectional comparative study was conducted from September 2018 to August 2019 at the Department of Physiology, University of Sindh in collaboration with Liaquat University Hospital Hyderabad. Four hundred pregnant females aged between 18 to 40 years, admitted to deliver a baby at Gynae and obstetrics department, LUMHS, Hyderabad/Jamshoro were selected by purposive random sampling, women aged below 18 and above 40, with multiple pregnancies, still births, threatened abortion having history of chronic disease, and with drug abuse were excluded from study. Females aged between 18-40 who were having singleton pregnancy were included in this study. After obtaining written consent, complete blood picture (CBC) was performed, in Diagnostic and Research Laboratory LUMHS, three parameters of anthropometry which include weight, length, and head circumference of the babies were measured. Results: The results were generated by using SPSS 21, for statistical data analysis. The prevalence of anemia was 206(51.5%). In anemic group 98(47.5%) babies born were low birth weight, and were less than 3rd percentile, and 15(7.2%) babies born were less than 3rd percentile length for age, the birthweight of babies in anemic mothers is 2.45kg±0.32 significantly (P. 0.0001) less than non-anemic group 3.09kg±0.66. The birth length of babies is 46.6cm ±2.30 significantly (P.0.0001) less than non-anemic group 48.1cm±1.19. Similarly, the head circumference was 32.5cm ±1.62 of the anemic mother’s babies, significantly (P. 0.0001) less than non-anemic group 33.3cm±0.63. Conclusion: It is concluded that the maternal hemoglobin plays an important role in the intrauterine growth of the neonates, affecting their anthropometric indices significantly. KEY WORDS: Anemia, anthropometry, birth weight, birth length, head circumference.